Health promotion and food insecurity: Exploring environmental sustainability principles to guide practice within Australia. (14th April 2019) - Nuttman, Sonia; Patrick, Rebecca; Townsend, Mardie; Lawson, Justin
Abstract: Issue addressed: The Australian health promotion sector has made significant advances in food security over the years through recognition of social and economic factors. The incorporation of ecological determinants within health promotion practice to address food insecurity, however, is uncommon. This paper explores the potential of health promotion to use environmental sustainability principles to guide the development of health promotion food security programs in Australia. Methods: A mixed‐methods approach guided by a pragmatic framework was adopted for this study. A national online survey (n = 61) and semi‐structured interviews (n = 16) targeting Australian health promotion practitioners was utilised. Triangulation involved seven stages to develop points of convergence and corroboration of the data. Results: Practitioners were adopting principles of environmental sustainability such as ecological integrity and biodiversity protection to guide food security practice. The use of such principles demonstrates their compatibility within health promotion practice. This study, however, reveals that environmental sustainability principles were a relatively new area of practice for health promotion practitioners. Conclusion: The possibilities for integrating health promotion and environmental sustainability principles are promising for addressing multifaceted issues inherent within food security practice. At present, a lack of principles exist for guiding the sector to address food security that is cognisant of both human health and the environment. So what?: This study indicates a lack of integration between environmental sustainability and health promotion principles to guide food security practice. It would be pertinent for the sector to consider the development of a set of principles that considers both health promotion and environmental sustainability to ensure future food security and planetary health. Capacity building of current practitioners and pre‐service graduates around the use of such principles to guide practice could assist the sector in this process.